Globalization, security, and the nation-state : paradigms in transition - Aydinli, Ersel, 1967-; Rosenau, James N. (SUNY series in global politics., 2005)
This volume studies the links among the concepts of globalization, security, and the authority of the nation state, drawing attention to why and how these three concepts are interrelated and why they should be studied together. Contributors explore the connections between security and global transformations, and the corresponding or resulting changes in state structures that emerge. Probing and extending existing paradigms, the book offers three regional cases studies: the periphery states of the Middle East and North Africa, the second world states of the Russian Federation, and the core states of the European Union. It concludes with three chapters that synthesize the above themes to identify corresponding changes in the patterns of international politics. Book jacket.